ANALISIS PEMBELAJARAN SAINS MADRASAH IBTIDAIYAH (MI) DALAM KURIKULUM 2013 - SHAWMI, AYU NUR (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2016)
The process of learning is at the core of the educational process as a whole with the teacher as the main role holder . Curriculum 2013 is the actualization of the curriculum in learning and competence and character formation of the students , it requires the activity of teachers to create and grow a variety of activities in accordance with the plans that have been programmed . Learning science or natural science is a learning-oriented activities on the natural environment. Learning aims to provide sensitivity and concern for the learners to be able to recognize more deeply about the natural environment . Through science learning is expected along with increased understanding of the natural environment and expected future generation born who are committed to create a prosperous life without forgetting the preservation of nature